“Preferencia varietal de Tagosodes orizicolus en 18 líneas avanzadas F4 de arroz tipo japónico (Oryza sativa L. ssp. Japónica), en época lluviosa en la zona de Babahoyo – Los Ríos”. - Silva Meza, Jerlyne Elizabeth (2019)
SUMMARY The present work of investigation on the "Preference varietal of Tagosodes orizicolus in 18 advanced lines F4 of rice type japonica (Oryza sativa L. ssp. Japónica)," was established in the sector of the CEDEGE Project, Hacienda Valle Verde, Babahoyo canton, province of Los Ríos. The varieties evaluated were: Plant height (cm), Panicle length (cm), flowering (days), No. of grains per panicle, No. of tillers per plot, No. of panicle per plot, Weight 1000 grains (gr), Adult population of Tagosodes orizicolus, Incidence of white leaf virus, Evaluation of mechanical damage of Tagosodes orizicolus, Yield per hectare (kg7ha), and the Random Complete Block Design (DBCA) was used with eighteen treatments and three repetitions. Likewise, the Tukey test was used at 95% probability. The results showed with respect to the plant height variable, that treatment 11 obtained an average of 115.42 cm, unlike treatment 4 that reached an average of 62.05 cm. Treatment 9 obtained the highest value of grains per panicle with an average of 158.67, the lowest value was recorded by treatment 4 with a value of 52.00 grains. Regarding the number of tillers, treatment 9 was observed, which reached an average of 231.00 tillers, however treatment 6 obtained a value of 119.67 tillers. As regards the panicle number, treatment 9 showed the highest value 187.33 panicles. Key Words: Rice - preference - subspecies japonica - segregates F4